Identifying employee skills in SMEs in the Republic of North Macedonia - Lozanoska, Aleksandra; Piperkova, Irina; Djambaska, Elizabeta (Association of Economists and Managers of the Balkans, 2020)
The main aim of this paper is to identify current levels of knowledge, skills and abilities of the SMEs’ employees in North Macedonia, vis-à-vis firms’ needs for knowledge and skills. This paper analyzes the current levels of employee job-specific, soft, digital and entrepreneurial skills on a sample of firms in North Macedonia. For the purposes of this research, the employees were classified in three categories: core employees, supporting employees and managers. The results of the research show that the main challenge regarding the soft skills refers to solving complex problems, capacity for job analysis and initiative. Adapting to new technologies is found to be the weakest aspect of digital skill among employees. Entrepreneurial skills related to risk taking, capacity to generate new ideas, creativity and innovation as well as flexibility at work are also considered to be a challenge.
Keywords: Employee skills, SMEs, North Macedonia